Marangoni-driven spreading of miscible liquids in the binary pendant drop geometry. Issue 42 (8th October 2019) - Koldeweij, Robin B. J.; van Capelleveen, Bram F.; Lohse, Detlef; Visser, Claas Willem
Abstract : The Marangoni-driven spreading dynamics of binary pendant droplets show a remarkable consistency with other geometries. A single power law describes a large array of Marangoni-driven spreading in binary liquid systems. Abstract : When two liquids with different surface tensions come into contact, the liquid with lower surface tension spreads over the other liquid. This Marangoni-driven spreading has been studied for various geometries and surfactants, but the dynamics of miscible liquids in the binary geometry (drop–drop) has hardly been investigated. Here we use stroboscopic illumination by nanosecond laser pulses to temporally resolve the distance L ( t ) over which a low-surface-tension drop spreads over a miscible high-surface-tension drop. L ( t ) is measured as a function of time, t, for various surface tension differences between the liquids and for various viscosities, revealing a power-law L ( t ) ∼ t α with a spreading exponent α ≈ 0.75. This value is consistent with previous results for viscosity-limited spreading over a deep bath. The universal power law L̃ ∝ t̃ 3/4 that describes the dimensionless distance L̃ as a function of the dimensionless time t̃ reasonably captures our experiments, as well as previous experiments for different geometries, miscibilities, and surface tension modifiers (solvents and surfactants). The range of this power law remarkably covers ten orders of magnitude in dimensionless time. This result enables engineering of drop encapsulation for various liquid–liquid systems.